Landscape : the printmaker's view. (London : Tate Gallery Publications Department, 1981)
Abrahams, Ivor ; Ackroyd, Norman ; Art & Language ; Atkinson, Terry ; Baldwin, Michael ; Auerbach, Frank ; Boshier, Derek ; Boumans, Bart ; Chaplin, Bob ; Cohen, Harold ; Dibbets, Jan ; Freedman, Barnett ; Fulton, Hamish ; Greenwood, Philip ; Gross, Anthony ; Hayden, Henri ; Hitchens, Ivon ; Hodgkin, Howard ; Kadishman, Menashe ; Lichtenstein, Roy ; Loker, John ; Long, Richard ; Millington, Terence ; Monro, Nicholas ; Nash, John ; Nash, Paul ; Nevinson, C.R.W. ; Piper, John ; Pissarro, Lucien ; Priest, Margaret ; Rothenstein, Michael ; Stevens, Norman ; Sutherland, Graham ; Tilson, Joe
Landscape : the printmaker's view, Tate Gallery, London, Gallery 61, May - June 1981
Engels
boek